STUDY REGARDING THE ORGANIZATION OF HUMAN RESOURCES AT S.C. AGROZOOTEHNICAL FARM S.A. - Daniela SIMTION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present study is intended for the management of the analysed company, which is concerned with the increase of the efficiency of the activity. Labor productivity has increased from one year to another. The efficiency in using human resources is the way of observing some correlations between the main objectives and the results obtained from their realization. The study of certain correlations, at the level of the selected society, shows that biggest increase in turnover was obtained through labor productivity, therefore by intensive and not extensive means.